Effects and determinants of Cross-Order Mergers and Acquisitions (CBMAs) in five East Asian countries / Song Saw Imm … [et al.] - Saw imm, Song (Research Management Institute (RMI), 2010)
Cross-border Mergers and acquisitions (CBMAs) form a large portion of foreign direct investment flows in developed world, and an increasing share in emerging markets especially to the Asian countries after Asian Financial Crisis in 1997/98. Various studies have been done on wealth effects and financial performance of firms in different countries and have yielded mixed results. This study covers CBMAs in five Asian countries most affected by the Asian financial crisis namely, Malaysia, Thailand, Indonesia, the Philippines, and Korea. Malaysia reported the highest number of CBMAs but a rather low percentage of CBMAs in proportion to total M&As. The majority of the CBMAs in these countries were in the financial sector, followed by the industrial and material sectors. Analysis on post-merger performance on a sample consisting of public listed firms with completed deals of more than ten percent of share acquisition by foreigners was performed using the event study method, key financial ratios and Tobin's q. From a sample of 94 targets for event study analysis and 114 targets for ratio analysis, the results for average abnormal returns of firms in Indonesia and Korea were inconclusive. However, the results for Malaysia, Thailand and the Philippines suggest that the market had reacted positively by adding value to the target firms upon merger announcements. The results show a marginal improvement in the performance or perceived growth opportunities as measured by the adjusted Tobin's q. The findings reflect the heterogeneity and complexity of the causes and effects of CBMAs in this region.